Konstruksi Diri Waria dan Lingkungannya Pasca Pandemi Covid-19: Transgender Self-Construction and Their Environment after the Covid-19 Pandemic - Lina Amiliya (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2024)
This study aims to analyze the impact of the Covid-19 Pandemic on transgender self-construction and their environment. This is based on the existence of new activity patterns that force people to adapt to the policies set by the government. One of them is waria, where self-construction and its environment have formed new habits as a result of the government's policy. the method used in this research is descriptive qualitative research. Data from interviews and observations were analyzed through three stages, namely reduction, data presentation and verification or drawing conclusions. The results of this study indicate that the construction built by transgender after the Covid-19 Pandemic is that transgender places himself in the position of transgender who has social anxiety and experiences a decline in the quality of religion. Meanwhile, in contrast to the construction of the environment given to transgender, waria is seen as having a positive image and having a high social and religious spirit.